Motivational interviewing as a positive response to high‐school bullying. Issue 5 (25th March 2018) - Cross, Donna S.; Runions, Kevin C.; Resnicow, Ken A.; Britt, Eileen F.; Gray, Caitlin
Abstract: Intervention approaches to bullying are largely preventive in nature, and even these have been shown to be ineffective, if not iatrogenic, with adolescents. Responses to bullying are limited to traditional punitive approaches or "no‐blame" approaches aiming to restore the relationship between the targeted students. Neither of these approaches may effectively engage the perpetrator of bullying at a motivational level, and we propose motivational interviewing (MI) as a means of promoting meaningful behavioral change among youths who bully. We provide a narrative review of MI and map its core features onto the extant literature on self‐reported motivations for bullying, highlighting the ways that MI fits with bullying and could serve as a potent solution that could be deployed by school psychologists and other student support staff members. Qualitative preliminary feedback and initial competency in MI from trained practitioners are presented as preliminary data from a cluster‐randomized control trial, documenting school staff perspectives on the integration of MI into their approach to bullying with recommendations for integrating MI into school settings.